PROFIL KEWIRAUSAHAAN SISWA MI MA’ARIF BULUSARI KALIKAJAR MELALUI PROJECT BASED LEARNING BERBASIS LITERA ANAPAKRA - Maulana Adi Sapurta, Ahmad Rifki; Khoiri, Ahmad; Putri Hanifah, Desty (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the entrepreneurial profile of students at MI Ma’arif Bulusari Kalikajar through the modification of Litera Anapakra as an innovative literacy-based learning medium. The background of this study is grounded in the urgency of instilling entrepreneurial values from an early age to develop independent, creative, and innovative student character in the era of the industrial revolution 4.0. This research employed a qualitative approach with a descriptive research design. The subjects of this study were 32 students of grades IV, V, and VI at MI Ma’arif Bulusari Kalikajar, with data collected through participatory observation, in-depth interviews, design product documentation, and field notes. The modification of Litera Anapakra in this study was implemented through three integrated phases: a literacy phase, an analytical-creative phase, and a logo design practice phase for dried chili products using the Canva application. The results revealed that the implementation of the modified Litera Anapakra effectively developed students’ entrepreneurial profiles encompassing five key dimensions: creativity, independence, responsibility, cooperation, and decision-making courage. A total of 78% of students produced original logo designs, all students (100%) completed their products on time, and a spontaneous cross-class mentoring phenomenon emerged as a manifestation of cooperative values and leadership. The use of Canva as a design platform proved to function as a creativity accelerator while simultaneously fostering a sense of ownership toward the entrepreneurial products created. This study contributes to enriching the model of entrepreneurship learning based on contextual digital literacy media that is relevant and applicable for the madrasah ibtidaiyah level. Keywords: entrepreneurship, elementary students, Litera Anapakra, creativity, logo design, Canva, basic education